VISUAL ANTHROPOLOGY OF THE CITY - Nade Genevska-Bracic (EtnoAntropoZum, 2016)
The visual documentation of the city was a lengthy process of research, which was the result of ethnological survey carried out in the city for many years. The process of exploring the various segments of the cultural and historical development of the city evolves and upgrades every year by observing the changes in its social-economic development. This is my personal insight (experiment) into visual anthropology, which is important from the present perspective.